Profiling Antibiotic Resistance in Acinetobacter calcoaceticus - Janiece S. Glover; Taylor D. Ticer; Melinda A. Engevik (MDPI AG, 2022)
Background: Acinetobacter spp. have emerged as troublesome pathogens due to their multi-drug resistance. The majority of the work to date has focused on the antibiotic resistance profile of Acinetobacter baumannii. Although A. calcoaceticus strains are isolated in the hospital setting, limited information is available on these closely related species. Methods & Results: The computational analysis of antibiotic resistance genes in 1441 Acinetobacter genomes revealed that A. calcoaceticus harbored a similar repertoire of multi-drug efflux pump and beta-lactam resistance genes as A. baumannii, leading us to speculate that A. calcoaceticus would have a similar antibiotic resistance profile to A. baumannii. To profile the resistance patterns of A. calcoaceticus, strains were examined by Kirby-Bauer disk diffusion and phenotypic microarrays. We found that Acinetobacter strains were moderately to highly resistant to certain antibiotics within fluoroquinolones, aminoglycosides, tetracyclines, and other antibiotic classes. These data indicate that A. calcoaceticus has a similar antibiotic resistance profile as A. baumannii ATCC 19606. We also identified that all Acinetobacter species were sensitive to 5-fluoroorotic acid, novobiocin, and benzethonium chloride. Conclusion: Collectively, these data provide new insights into the antibiotic resistance in A. calcoaceticus and identify several antibiotics that could be beneficial in treating Acinetobacter infections.